The Risks of Pregnancy and the Consequences among Young Unmarried Women Working in a Free Trade Zone in Sri Lanka - Hettiarachchi, T. (My University, 2001)
The primary health care system in Sri Lanka has an international reputation for its contributions to reducing the rates of infant and maternal morbidity and mortality. These results have been achieved in part through a comprehensive system of early identification of expectant mothers, careful follow-up and monitoring, almost universal hospital deliveries, postpartum follow-up for three months after delivery, an effective immunization programme, nutrition supplements and the reporting of infectious diseases. A key to this system is the “public health midwife” (PHM) who identifies pregnant mothers, ensures their regular attendance at maternal and child health (MCH) clinics, makes monthly home visits, advises pregnant mothers on nutrition and health, facilitates hospital admission for delivery and responds to emergencies. They also provide postnatal follow-up of mother and child (Ministry of Health and Indigenous Medicine, 1998). In a typical rural community, a PHM is responsible for an average of 3,000 families and addresses the needs of 25-30 expectant mothers a year. This article explores the dynamics of a situation in which the demands on the PHM have expanded tenfold, resulting in significant risks to pregnant women and infants. This situation has arisen following the formation of a “free trade zone” (FTZ) associated with the international airport north of Colombo. That FTZ has dramatically increased the population of the adjoining residential communities from about 9,000 to a current population of 70,000. In addition, the transition has changed the sex ratio from an approximately even balance of females to males to a proportion of nine females for every male. Almost all of these women are unmarried and are mostly aged between 18 and 24. The article aims to identify the factors that contribute to a high rate of premarital pregnancies among FTZ workers and the implications of those pregnancies for the effective delivery of services through the MCH system.